What Are the Predictors of Intracranial Aneurysm Rupture in Indonesian Population Based on Angiographic Findings? Insight from Intracranial Aneurysm Registry on Three Comprehensive Stroke Centres in Indonesia - Jovian P. Swatan; Achmad F. Sani; Dedy Kurniawan; Hermanto Swatan; Shakir Husain (Stroke Research and Treatment)
Objectives. What are the Predictors of Intracranial Aneurysm (IA) Rupture based on angiographic findings among patients in Indonesia’s Population Based on Angiographic Findings. Materials and Methods. We conducted a cross-sectional study on subjects with IA not caused by congenital aetiologies or other vascular malformations with cerebral angiography performed from January 2017 to January 2021. Demographic data and aneurysm profile, which include aneurysm count, size, location, and rupture event, were collected. The correlation between risk factors and IA rupture events was determined using bivariate and multivariate analysis. Results. From 100 angiography data (33 males and 67 females), the mean subject age is 51.94±10.78. We observe a total of 121 IAs from all subjects. Most of the IAs are in the anterior circulation (104 aneurysms, 85.96%), have small size (77 aneurysms, 63.64%), and are found in ruptured conditions (90 aneurysms, 74.38%). Males have a greater aneurysm count (1.36±0.74 vs. 1.13±0.55, p=0.036) and larger aneurysm size (p=0.002). Aneurysm size is significantly correlated with its location (p=0.008). Medium size (p=0.019; OR 2.62, 95% CI 1.08-6.36) and location other than the internal carotid artery are associated with increased rupture event. Multivariate analysis revealed that gender (p=0.031; aOR 5.37, 95% CI 1.17-24.70) is a significant risk factor of IA rupture event. Conclusion. IA profiling will enable clinicians to determine the risk of rupture and treatment plans for the Indonesian population. Further studies with a larger sample size are required to confirm these findings.